What Would Hercules Do? Lessons for Autistic Children Using Classical Myth - Deacy, Professor Susan (Our Mythical Childhood, 2023)
One day, according to the Ancient Greek author Xenophon, the hero Hercules "went out to a quiet place and sat, pondering". This book explores what happened here and how and why it can resonate with autistic young people. The book presents a set of ten lessons, each dealing with an aspect of what happened when Hercules entered the quiet place, met two women (or goddesses, or personifications...) and was tasked to make a choice between two paths, literal and metaphorical. The lessons deal, too, with particular dimensions of autism, including: communicating, emotions, decision-making, sensory experiences, planning and interests. This pathbreaking book should be of particular interest to professionals and practitioners looking to utilize the appeal of mythology in their work with autistic children and academics in areas such as education, Classics and literature interested in the experiential application of their subject.